2021
DOI: 10.1016/j.carpta.2021.100052
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrates-based diagnosis, prophylaxis and treatment of infectious diseases: Special emphasis on COVID-19

Abstract: COVID-19 pandemic is taking a dangerous turn due to unavailability of approved and effective vaccines and therapy. Currently available diagnostic techniques are time-consuming, expensive, and maybe impacted by the mutations produced in the virus. Therefore, investigation of novel, rapid, and economic diagnosis techniques, prophylactic vaccines and targeted efficacious drug delivery systems as treatment strategy is imperative. Carbohydrates are essential biomolecules which also act as markers in the realization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 120 publications
(108 reference statements)
0
7
0
1
Order By: Relevance
“…After the attack of viruses in the human body through the respiratory tract, they usually utilize sugar chains (glycans) present on the surface of host cells. Thus, the virus is covered by glycans resistant to mutation through its development process 41 . In this research, the band correlated to carbohydrates showed a higher expression in the COVID-19 group, probably due to the high concentration of spike glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…After the attack of viruses in the human body through the respiratory tract, they usually utilize sugar chains (glycans) present on the surface of host cells. Thus, the virus is covered by glycans resistant to mutation through its development process 41 . In this research, the band correlated to carbohydrates showed a higher expression in the COVID-19 group, probably due to the high concentration of spike glycoprotein.…”
Section: Discussionmentioning
confidence: 99%
“…Though direct relationship between rice consumption and COVID-19 severity and hospitalization is not evident, but, rice consumption might be beneficiary for avoiding massive damage by this disease. As carbohydrates are closely associated with immune components at molecular level, carbohydrate rich food is suggested for COVID-19 patients in different studies (Kumbhar et al, 2021). Fish and meat both contain protein which might be the factor for less hospitalization and severity among the consumers.…”
Section: Discussionmentioning
confidence: 99%
“…At the molecular level, carbohydrates are intricately linked with immune components. Thus, carbohydrate-based systems potentially constitute features to combat COVID-19 [48]. In addition, carbohydrates depict antifungal, antimicrobial and antiviral attributes, which make them propitiously relevant to morphologically engage SARS-CoV-2 in the provision of vaccines and therapeutic agents.…”
Section: Diet Control and Therapeuticsmentioning
confidence: 99%